The Question of A “Spirit of Medieval Philosophy”: Étienne Gilson Today - Soto-Bruna, María Jesús; Ormazabal Echeverría, Javier (Scripta Mediaevalia, 2025)
What was Étienne Gilson referring to when he spoke –at the beginning of the 20th century– of the existence of a “spirit of medieval philosophy”? Is it not true that research into the so-called medieval thought already had sufficient elements to find at least four types of speculation in the so-called medieval period? Let us remember: Judaism, the Neoplatonic current in its various phases, Syriac works and their own interpretation of Plato and Aristotle, the influential Arab thought, with its respective rethinking of Greek philosophers. This article analyzes the elements that contribute to this determination and its current validity.